Dyadic Associations Between Physical Activity and Depressive Symptoms in Older Adults with Musculoskeletal Conditions and Their Spouses. (23rd July 2014) - Monin, Joan K.; Chen, Baibing; Stahl, Sarah T.
Abstract: This study examined the association between physical activity of older individuals with musculoskeletal conditions (IMCs) and their spouses' physical activity, how physical activity related to one's own and one's partner's depressive symptoms, and whether the similarity of partners' physical activity related to each partner's depressive symptoms using the actor–partner interdependence model. Seventy‐seven dyads completed self‐report measures of physical activity, depressive symptoms and potential covariates (socio‐demographics, physical health conditions and marital satisfaction; IMCs' functional impairment and pain; and spouses' support‐related stress). As hypothesized, we found a positive association between the IMC's and the spouse's physical activity. Also, spouses had more depressive symptoms when IMCs engaged in less physical activity. However, for both partners, one's own physical activity was not significantly associated with one's own depressive symptoms. The spouse's physical activity was also not significantly associated with the IMC's depressive symptoms, and the similarity between partners' physical activity did not significantly relate to either partner's depressive symptoms. Our findings suggest that interventions that help increase the physical activity of both partners, but particularly IMCs, may benefit spouses' well‐being. Copyright © 2014 John Wiley & Sons, Ltd.